Response of the metabolic and autophagy pathways in Mytilus under starvation - Xie, Bing; Chen, Chuan-yue; Zhang, Xiaolin; Li, Si-yuan; Gu, Zhong-qi; Huang, Ji; He, Jian-yu; Qi, Peng-zhi; Guo, Bao-ying; Liao, Zhi; Yan, Xiaojun (Frontiers in Marine Science, 2022)
Being an industrially valuable species of bivalve, Mytilus is widespread in the area around the eastern coast of China. Starvation is an environmental stress that mussels often encounter in their growth. However, few report carried out on the physiological and biochemical response and molecular regulation and adaptation mechanism of mussels under starvation. To illustrate the molecular mechanism of hosts of Mytilus to starvation, the gill transcriptome was used for analysis before and after 9 days of starvation in Mytilus using the Illumina/HiSeq-2000 deep sequencing platform, accompanied by the study of differentially expressed genes (DEGs). In total, 42.137 GB of clean data were obtained from six sample libraries, the average amount of clean data of each sample is 7.023 GB, and 58,540 unigenes that average 780 bp in length were assembled. Unigenes were illustrated by commenting them against the NR, Swiss-Prot, Pfam, String, GO and KEGG databases. After 9 days of starvation, 2,188 and 2,672 genes were determined to be significantly up- or down-regulated expression genes, separately. Amongst, 4,860 genes were associated with 260 pathways, contains vital enrichment pathways, such as “Metabolic”, “PI3K-Akt signaling pathway”, “Phagosome”, “Apoptosis” and “Lysosome”. In inclusion, autophagy cells were investigated by an electron microscopy, alongside further observations of the expression of autophagy-related genes in gill tissue before and after starvation. The data indicates that the amount of autophagosomes increased and found that atg2, atg6 and atg13 were significantly up-regulated. These results indicated that Mytilus may use autophagy to cope with their damage after starvation. With our research results, we have contributed to a deeper understanding of the role of the molecular mechanisms of immune defence in Mytilus under environmental stress, which has given insights into mussel breeding and the understanding of the molecular mechanisms of Mytilus immune system.